Initial psychometric evidence of a scale to quantify the Relative frequency with which adolescents observe events of violence - Olivas Ugarte, Lincol Orlando (2020)
This study was carried out with the aim of building a scale to quantify the relative frequency with which adolescents observe acts of violence. 860 high school students participated, 433 men and 427 women, aged 12 to 17 years. The 15 items showed adequate homogeneity, discrimination and community indexes. We found evidence of validity in relation to life satisfaction and empathy. The exploratory factor analysis reported that the five factors: observation of violence on the Internet, TV, street, school and home, explain 77.6% of variance. Confirmatory factor analysis showed the model fit of five correlated factors (CFI = .969, RMSEA = .051 and SRMR = .031). Finally, the coefficients Alpha ordinal (.964) and Omega (.957) demonstrate the reliability of the EOVA scale.